An experimental study of crystalline basalt dissolution from 2 ≤ pH ≤ 11 and temperatures from 5 to 75 ºC - Gudbrandsson, S.; Wolff-Boenisch, Domenik; Gislason, S.; Oelkers, E. (Pergamon-Elsevier Science Ltd, 2011)
Steady-state element release rates from crystalline basalt dissolution at far-from-equilibrium were measured at pH from 2 to 11 and temperatures from 5 to 75 °C in mixed-flow reactors. Steady-state Si and Ca release rates exhibit a U-shaped variation with pH where rates decrease with increasing pH at acid condition but increase with increasing pH at alkaline conditions. Silicon release rates from crystalline basalt are comparable to Si release rates from basaltic glass of the same chemical composition at low pH and temperatures ≥ 25 °C but slower at alkaline pH and temperatures ≥ 50 °C. In contrast, Mg and Fe release rates decrease continuously with increasing pH at all temperatures. This behaviour is interpreted to stem from the contrasting dissolution behaviours of the three major minerals comprising the basalt: plagioclase, pyroxene, and olivine. Calcium is primarily present in plagioclase, which exhibits a U-shaped dissolution rate dependence on pH. In contrast, Mg and Fe are contained in pyroxene and olivine, minerals whose dissolution rates decrease monotonically with pH. As a result, crystalline basalt preferentially releases Mg and Fe relative to Ca at acidic conditions. The injection of acidic CO2-charged fluids into crystalline basaltic terrain may, therefore, favour the formation of Mg and Fe carbonates rather than calcite. Element release rates estimated from the sum of the volume fraction normalized dissolution rates of plagioclase, pyroxene, and olivine are within one order of magnitude of those measured in this study.